Animals for the mayor: Barcelona's zoo in the making of local policies and national narratives (1957–73). (September 2022) - Carandell Baruzzi, Miquel
From 1957 to 1973, Barcelona Zoo was transformed from a small-scale, antiquated establishment harboring very few animals, a place that was still in a poor condition following the Spanish Civil War, into a new, larger, modern, and internationally recognized institution that included up-to-date animal enclosures and that boasted one of the first dolphinariums in Europe, as well as a famous white gorilla as its icon. From its very beginning, this renovation involved an intense popularization campaign. In this paper, by describing the public discourse generated throughout this transformation and by analyzing the roles played by Antoni Jonch, the director of the zoo at that time; Josep Maria de Porcioles, the then-mayor of Barcelona; and General Francisco Franco, the Spanish dictator who was head of state during this period, I will highlight how the context of the dictatorship not only authorized the new Barcelona Zoo but is, in fact, crucial to its understanding. The narratives that surrounded the renovation of the zoo focused on its civic and educational purpose, with a firm emphasis on modernity . The zoo was a modern space for learning about animals in order to become better people. These narratives were not only suitable to the policies, ideas, and aims of Porcioles' City Council and Franco's dictatorial regime; in fact, they completely matched them. Both local and national governments benefited from the restructuring of Barcelona Zoo and from its public discourse as a tool for social control and an instrument for their own propaganda, legitimation, and perpetuation.